THE ROLE OF A CULTURE OF PEACE IN ENSURING PUBLIC SAFETY (American Journal of Pedagogical and Educational Research, 2023)
The article reveals the meaning of the concepts of public safety and culture of peace, their relationship, as well as the role of a culture of peace in ensuring public safety.